Does an Agency‐Type of Audit Model Fit a Stewardship Context? Evidence from Performance Auditing in Dutch Municipalities. (April 2016) - Tillema, Sandra; ter Bogt, Henk J.
Abstract: The degree of auditor independence is an important issue in the performance auditing literature. However, little attention has been paid to the influence of the context in which an audit body operates. This paper investigates how an audit model with a high degree of auditor independence, which is consistent with agency theory's rather formal view of relationships in organizations, functions in a context with more informal relationships, as implied by stewardship theory. Based on two case studies and a survey, the paper concludes that Dutch councilors are more satisfied with audit reports if in their municipality there is a fit between context and audit model.